Problems and Trends in Human Trafficking in Republic of Bulgaria - Bankova, Viola (Research Papers, 2023)
Human trafficking, particularly of women and children, is one of the current/pressing themes nowadays. Even though slavery as such was prohibited more than 200 years ago, in recent times, strikingly similar practices have emerged. Annually, between 700 000 and 4 000 000 men, women and children are bought, sold, shipped and kept in captivity against their will and under circumstances which could safely be described as slavery. The aim of this article is to analyze the problems associated with human trafficking in Bulgaria in order to propose measures for improving counteraction against it. The results of this study are significant for formulating prevention and combat strategies against human trafficking in Bulgaria.